RELEVANSI KONSEP PENDIDIKAN ISLAM WALI SONGO TERHADAP PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA: The Relevance Of The Wali Songo's Islamic Education Concept To The Profile Of Pancasila Students In The Independent Curriculum - Arofi, Mohammad Fahmi; Salamah, Umi; Zuhdi, Zaenu (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to examine the concept of Islamic education as taught by Wali Songo, as presented in Agus Sunyoto's Atlas Wali Songo, and to analyze its relevance to Pancasila Student Profile in the Merdeka Curriculum. This qualitative research employs a library research method with content analysis. Data were collected from main book and supported by secondary literature. Findings show that Wali Songo’s Islamic education is inclusive, transformative, and contextual. Their adaptive approach to local culture, Sufi-based values, and the principles of tadrij and adaamul haraj align with the six core characteristics of the Pancasila Student Profile: faith and devotion to God Almighty, collaboration, independence, critical reasoning, creativity, and global diversity. These findings suggest that educational legacy of the Wali Songo offers a conceptual foundation to enhance the character development of Indonesian students